The Role of Grass MUTE Orthologues During Stomatal Development - Serna, Laura (Frontiers in Plant Science, 2020)
Gas exchange between the plant and the atmosphere takes place through stomatal pores formed by paired guard cells. Grasses develop a unique stomatal structure that consists in two dumbbell-shaped guard cells flanked by lateral subsidiary cells. This structure confers a very efficient gas exchange capacity, which may have contributed to their extraordinary evolutionary success. Recent works have identified orthologues of Arabidopsis MUTE in three grass species: BdMUTE in Brachypodium distachyon, BZU2/ZmMUTE in maize and OsMUTE in rice. These genes induce the recruitment of subsidiary cells, and it appears to rely upon the ability of intercellular movement, from the guard mother cell to subsidiary mother cells, of the proteins encoded by them. Unexpectedly, this function of these grass MUTE genes contrasts with that of Arabidopsis MUTE, which promotes guard mother cell identity. These MUTE orthologues also appear to control guard mother cell fate progression, with the action of BdMUTE being less severe than those of BZU2/ZmMUTE and OsMUTE. The emerging picture unravels that grass MUTE genes have not only diverged, due to neo-functionalization, from Arabidopsis MUTE, but also among them.